Metabolomics analysis of anaphylactoid reactions induced by Xueshuantong injection in normal and immunocompromised mice - Xiaoqian Guo; Xiaoqian Guo; Chi Zhang; Chi Zhang; Yingyu Li; Yingyu Li; Yingyu Li; Wen Wen; Wen Wen; Wen Wen; Yinghui He; Feng Tang; et al. (Frontiers in Pharmacology)
BackgroundXueshuantong injection (Lyophilized) (XSTI) is widely used to treat cardiovascular and cerebrovascular diseases. However, anaphylactoid reactions (ARs) are frequently reported as one of its side effects, and the mechanisms of ARs and their relationship with the different immune status are still not well understood.PurposeThis article aims to examine the sensitizing effect of XSTI, explore the impact of normal and immunocompromised states on ARs, and analyze AR-related metabolic pathways by metabolomics.MethodsAn immunocompromised mouse model was established through intraperitoneal injection of cyclophosphamide (CTX). Normal and immunocompromised mice were then treated with normal saline (NS), histamine (HIS), and XSTI, respectively. Behavioral responses, auricle blue staining, and Evans blue (EB) exudation were used as indices to evaluate the sensitization of XSTI on both normal and immunocompromised mice. Subsequently, ARs models with different immune statuses were established, and validated by measuring four serum indicators using enzyme-linked immunosorbent assay (ELISA). Finally, LC-MS metabolomics analysis was performed on mouse serum to evaluate the metabolic pathways.ResultsThe intensity of ARs induced by XSTI in mice was found to increase with the administered dose, with normal mice exhibiting higher AR intensities compared to immunocompromised mice. Metabolomic analysis revealed significant metabolic changes in XSTI-treated mice. The metabolic pathways predicted from these different metabolites include biotin metabolism, histidine metabolism, glycerolipid metabolism, bile secretion, arachidonic acid metabolism, sphingolipid metabolism, niacin and nicotinamide metabolism, tryptophan metabolism, steroid biosynthesis, and arginine and proline metabolism.ConclusionResearch indicated that the sensitization of XSTI is dose-dependent, and mice with weakened immune functions exhibit lower sensitivity. Through metabolomics research, the differential metabolites in mice were analyzed, and the metabolic pathways inducing ARs were predicted. This study offers guidance on safe medication from the perspective of organism susceptibility and lays a foundation for research on the potential mechanisms of ARs.